Adsorption and Interaction of 2-Aminopyridine with Loughlinite (Na-Sepiolite) from Anatolia - AKYUZ, SEVIM; AKYUZ, TANIL (Asian Journal of Chemistry, 2010)
FT-IR spectroscopy has been used to characterize adsorption and interaction of 2-aminopyridine by loughlinite, which belongs to palygorskite-sepiolite group of phyllosilicates class of clay minerals. The spectroscopic results indicate generation of 2-aminopyridinium cations. Cationic and neutral surface species adsorbed on loughlinite are coordinated to Bronsted acidic sites and surface hydroxyls (by H-bonding interaction through pyridine ring nitrogen lone pairs), respectively. It must be noted that the adsorption of 2-aminopyridine affected the hydroxyl group vibrations of loughlinite.